The attitudes of healthcare professionals in surgical operations on the use of artificial intelligence and its integration into the operating room - Zorman, Lidija; Farkaš-Lainščak, Jerneja (Anali PAZU, 2024)
Artificial intelligence has significant potential to improve the quality and efficiency of healthcare in surgical operations. A study conducted in the General Hospital Murska Sobota in 2023 examined the attitudes of healthcare professionals in surgical operations towards the use of artificial intelligence. The survey included 120 respondents (response rate 64.1%). One-third supported the integration of artificial intelligence in operating rooms. The main advantage they see in its use is the absence of emotional exhaustion (41.6%). However, they highlighted its limited ability to adapt and solve unexpected situations as a disadvantage (57.1%). In the next ten years, they expect its development in support services for operating rooms (39%). Ethical dilemmas focus on the responsibility for its use. The majority of respondents (54.5%) believe that legal responsibility will be assumed by the employed healthcare professionals in surgical operations. According to the respondents (63.7%), artificial intelligence cannot replace the role of a healthcare professional in the operating room. Further research could explore education about artificial intelligence and the development of ethical guidelines for its use.
Keywords: surgery; surgeon; nurse; modern technology; intelligent systems